A unified DNA sequence and non‐DNA sequence mapping model of complex traits. (8th June 2019) - Zeng, Yanru; Zhu, Xuli; Chen, Chixiang; Banerjee, Kalins; Sun, Lidan; Yu, Weiwu; Zheng, Bingsong; Wu, Rongling
Summary : Increasing evidence shows that quantitative inheritance is based on both DNA sequence and non‐DNA sequence variants. However, how to simultaneously detect these variants from a mapping study has been unexplored, hampering our effort to illustrate the detailed genetic architecture of complex traits. We address this issue by developing a unified model of quantitative trait locus (QTL) mapping based on an open‐pollinated design composed of randomly sampling maternal plants from a natural population and their half‐sib seeds. This design forms a two‐level hierarchical platform for a joint linkage‐linkage disequilibrium analysis of population structure. The EM algorithm was implemented to estimate and test DNA sequence‐based effects and non‐DNA sequence‐based effects of QTLs. We applied this model to analyze genetic mapping data from the OP design of a gymnosperm coniferous species, Torreya grandis, identifying 25 significant DNA sequence and non‐DNA sequence QTLs for seedling height and diameter growth in different years. Results from computer simulation show that the unified model has good statistical properties and is powerful for QTL detection. Our model enables the tests of how a complex trait is affected differently by DNA‐based effects and non‐DNA sequence‐based transgenerational effects, thus allowing a more comprehensive picture of genetic architecture to be charted and quantified. Significance Statement: Complex traits are inherited through both DNA sequence and non‐DNA sequence variants, but how to map these variants simultaneously has been a major challenge. We develop a unified framework for modeling and estimating genetic, maternal, and genetic imprinting effects of individual quantitative trait loci (QTLs), helping to illustrate the genetic architecture of complex traits.